A real-time locating system for localization of high-speed mobile objects - Minhyuk Kim; Sekchin Chang (International Journal of Distributed Sensor Networks)
This article addresses a novel real-time locating system for localization of high-speed mobile objects in fading environments. The proposed locating system exploits time difference of arrival measurements based on ultra-wideband signals. However, the ultra-wideband signals cause a frequency-selective fading due to their short time duration, which induces severe inter-symbol interference. Moreover, high-speed objects cause fast fading due to large Doppler spread. Therefore, the fading cases considerably reduce the localization performance. The presented locating system relies on a new localization approach in order to overcome the fading issues, which utilizes a modification of extended Kalman filtering. Especially, the suggested locating method works well even in the zero time difference of arrival case, which occurs due to a very deep fading. Experiment results verify that the proposed real-time locating system gives excellent localization performance in severe fading environments. The results also exhibit that the presented locating system is superior to the conventional locating systems in the localization of high-speed mobile objects under fading environments.